SHЕVАLАR VА TАRIХIY-ETNОLISОNIY JАRАYONLАR (Nаmаngаn shеvаlаri misоlidа) - Usmоnоv Musurmоn Mаmirаliyеvich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article discusses the ethnic groups that played an important role in the formation of the dialects of the Namangan region and some of its regions, their role in historical processes, as well as their modern status in the dialects.